1988
DOI: 10.1111/j.1365-2044.1988.tb06637.x
|View full text |Cite
|
Sign up to set email alerts
|

The nasocardiac reflex

Abstract: SummaryThe oculocarcliac r~f l e s is well tiescribed and rect~gnisrd in anacstlzesiu. The nasocumiuc reflies is ILJSS bvcll-known. We describe u clinical marzifestution of this reJlex and describe the relevant m a t o r n j~. This w f l e .~ rmq' be obturided during general anaesthesia. ( h i r i g generul unuesthesiu. Key wordsSitrpr-j,; car. nose and throat Coniplications; dysrhythniia.The oculocardiac reflex is well described and recognised in anaesthesia.' The nasocardiac reflex3 is less well-known. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…We stimulated the nasal mucosa at a frequency of 100∫10 Hz for three 2-s durations over 10 s intermittently because in the preliminary experiments we observed that the longer duration of stimulation did not increase the occurrence of NBMR, but increased the likelihood of nasal bleeding. We did not observe any untoward bradycardia or hypotension in any of our patients due to nasal stimulation, as reported previously (15,16).…”
Section: Discussionsupporting
confidence: 89%
“…We stimulated the nasal mucosa at a frequency of 100∫10 Hz for three 2-s durations over 10 s intermittently because in the preliminary experiments we observed that the longer duration of stimulation did not increase the occurrence of NBMR, but increased the likelihood of nasal bleeding. We did not observe any untoward bradycardia or hypotension in any of our patients due to nasal stimulation, as reported previously (15,16).…”
Section: Discussionsupporting
confidence: 89%
“…Fourthly, previous studies have shown that nasal intubation can stimulate the nasocardiac reflex, which is a vagal reflex and contributes to the significant bradycardiac response associated with the stimulation of the nasal mucosa [5,8, 12].…”
Section: Discussionmentioning
confidence: 99%
“…A search of the literature reveals reports describing various nasocardiac reflexes with a neurological basis in the trigeminovagal arc [10,[13][14][15][16]. These reports document that stimulation of the nasal mucosa may elicit a host of responses including apnoea, closure of the larynx, bradycardia, arrhythmias, vasomotor changes and sudden death [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…Death after trivial nasal stimulation, for example sneezing, has been reported in patients with myocardial disease [14,15]. Baxandall and Thorn [16] have reported profound bradycardia in an anaesthetized patient during turbinate bone manipulation. These authors describe the maxillary division of the trigeminal nerve (the innervation of the turbinates) as the afferent limb of this nasocardiac reflex.…”
Section: Discussionmentioning
confidence: 99%